Stylistics and Pragmatics of Artistic Ironic Discourse (English and French Languages) - M. S. Sheveleva (Научный диалог, 2022)
The article is devoted to the display of the stylistic peculiarities of literary ironic discourse in modern English and French prose. The empirical basis of the research is built on the corpus of text fragments containing ironic statements selected from literary works in English and French. The relevance of the study is accounted for by the insufficient study of the interconnections between verbal components and conceptual background of irony — the mental mechanism of second-order empathy — as well as the need to confirm the status of irony as a speech strategy of encouragement, incentive, self-defense, censure, ridicule, discredit, self-justification, self-representation or self-abasement, which is verbalized in fiction literature, thanks to the involvement of a number of stylistic devices of a semantic and syntactic sense. It is shown that in addition to linguistic means that objectify the conceptual structure of an ironic utterance and deictic units that reveal the order and logic of organizing information at the level of second-order empathy, fictional ironic discourse (both English and French) is brightly colored with figurative and expressive means of language, which actualize through ambiguous, voluminous, image-forming semantics and expressive syntax. In the course of comparative analysis, it has also been found out that the French-language fictional ironic discourse has a higher density of stylistic devices and is more expressive than the English-language one.